Efeitos da temperatura e manejo do cálcio sobre o miocárdio ventricular do teleosteo neotropical Prochilodus lineatus - Costa, Telma Aparecida (2005)
The present study anlyzed the in vivo and in vitro responses of the myocardium obtained from Prochilodus lineatus acclimated at 25 ºC and tested at 25 and 35 ºC. The in vivo heart rate (fH bpm) was measured during acute transitions in temperature and subsequent return to 25º C. ECG recordings (lead DI of the electrocardiography) were obtained of electrodes at cardiac region. Recordings of the isometric contraction force (Fc %) and time-dependent parameters (TPT time to peak tension; THR time to half relaxation) were obtainded in vitro from ventricle rings electrically paced in response to stimulation frequency, temperature, extracelular Ca2+, adrenaline and ryanodine (blocker of the sarcoplasmic reticulum SR). The species showed a significant increase in the fH during the transition from 25 to 35º C, showing the importance of the chronotropic adjustments in response to thermal alterations and a great tolerance and adaptation to different thermal conditions. The species did show significant decreases in the twitch force (Fc) development by the ventricular strips during the increases of temperature. The addition of crescent Ca2+ concentrations to the medium evidenced the importance of the extracellular Ca2+ as showed by the Fc increases at both 25 and 35º C. Concomitant increases in in TPT and THR here recorded at 25 ºC while at 35º C, such increases were observed only in TPT. Adrenaline caused positive inotropism only at 35º C, without effect on time-dependent parameters. The post rest tension was conducted with and without 10 µM ryanodine in the medium. A significant post rest potentiation was recorded for at 25 and 35o C These post rest potentiations were inhibited by ryanodine. The impact of increases in the imposed contraction frequency caused a decline of the force and an increase in resting tension (RT) at both temperatures. In conclusion, an important fraction of the activator Ca2+ in P. lineatus seems to derive from intracellular stores (RS). However, this species also depends on extracellular sources of Ca2+, which provide more flexibility to modulate the contraction force.